Effect of an anti-methanogenic supplement on enteric methane emission, fermentation, and whole rumen metagenome in sheep - Malik, Pradeep Kumar; Trivedi, Shraddha; Kolte, Atul Purushottam; Mohapatra, Archit; Bhatta, Raghavendra; Rahman, Habibar (Frontiers in Microbiology, 2022)
A study was conducted to investigate the impact of an anti-methanogenic product supplementation on enteric methane emissions, whole rumen metagenome and ruminal fermentation in sheep. Twelve adult male sheep were randomly divided into two groups of six animals each. Animals were fed ad libitum on a total mixed ration either without (CT) or with anti-methanogenic supplement (HD). The anti-methanogenic supplement contained 22.1% tannic acid in 3:1 ratio of condensed and hydrolysable tannins. The supplementation of product revealed a significant reduction in daily enteric methane emission (21.9 vs. 17.2 g/d) and methane yield (23.2 vs. 18.2) without affecting the nutrient intake and digestibility. However, the propionate concentration in HD group was significantly higher than the CT group. On the contrary, the ammonia nitrogen concentration was lower. The anti-methanogenic supplement significantly decreased the ruminal protozoa in HD group. Whole rumen metagenome analysis revealed that the core bacterial (Bacteroidetes and Firmicutes) and archaeal communities (Methanobrevibacter and Methanosarcina) were comparable between the CT and HD groups. However, the supplementation of anti-methanogenic product led to a considerable reduction in the abundance of Proteobacteria, whereas the abundance of Lentisphaerae was greater. The supplementation significantly decreased the abundances of Methanocaldococcus, Methanococcoides, Methanocella, and Methanoregula methanogens. Total 36 KO related to methanogenesis were identified in this study. The activities of formate dehydrogenase (EC 1.8.98.6) and tetrahydromethanopterin S-methyltransferase (EC 2.1.1.86) were significantly lowered by the anti-methanogenic product supplementation in sheep. In conclusion, the anti-methanogenic supplement has potential to decrease enteric methane emission (~22%) at the recommended level (5% of DM) of supplementation. The contribution of minor methanogens vulnerable to the supplementation to rumen methanogenesis is not known; hence, the culturing of these archaea should be taken on priority for determining the impact on overall rumen methanogenesis.